2014
DOI: 10.1159/000363019
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel -Like Factor 8 is a Stress-Responsive Transcription Factor that Regulates Expression of HuR

Abstract: Background/Aims: HuR is an RNA-binding protein that regulates the post-transcriptional life of thousands of cellular mRNAs and promotes cell survival. HuR is expressed as two mRNA transcripts that are differentially regulated by cell stress. The goal of this study is to define factors that promote transcription of the longer alternate form. Methods: Effects of transcription factors on HuR expression were determined by inhibition or overexpression of these factors followed by competitive RT-PCR, gel mobility sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
(83 reference statements)
1
2
0
Order By: Relevance
“…In our study, we have also confirmed the regulation of KLF9 mRNA by HuR. Interestingly, it has been proven that KLF8 (another transcription factor of the KLF family) regulates the expression of HuR(Govindaraju and Lee, 2014). Similarly, there may be a regulatory correlation between HuR and KLF9 in SCI, which could provide new insights for the treatment of SCI.Notably, we acknowledge the limitations of the study: (I) The study was specific to binding mRNAs, and onlyKLF9 was verified; thus, validation of other mRNAs is needed.…”
supporting
confidence: 85%
“…In our study, we have also confirmed the regulation of KLF9 mRNA by HuR. Interestingly, it has been proven that KLF8 (another transcription factor of the KLF family) regulates the expression of HuR(Govindaraju and Lee, 2014). Similarly, there may be a regulatory correlation between HuR and KLF9 in SCI, which could provide new insights for the treatment of SCI.Notably, we acknowledge the limitations of the study: (I) The study was specific to binding mRNAs, and onlyKLF9 was verified; thus, validation of other mRNAs is needed.…”
supporting
confidence: 85%
“…First of all, KLF4 is dispensable for early development [ 7 9 ]. Moreover, when KLF4 is expressed in adult somatic cells with other Yamanaka factors [ 10 , 11 ], KLF4 has been shown to promote the formation of induced pluripotent stem (IPS) cells [ 12 ]. For example, KLF4 is found to suppress cell proliferation through modulation of p21Waf1/Cip1 [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Krüppel-like factor (KLF) 8 is a member of the KLF family of transcription factors that contain three C2-H2 zinc fingers in the C-terminal DNA-binding domain, a nuclear localization signal, and a distinct N-terminal domain [9,10]. KLF8 is frequently upregulated in several types of cancer, including hepatocellular carcinoma (HCC), renal carcinoma, and breast, ovarian, and gastric cancers, and plays an important role in a wide range of biological processes, including oncogenic transformation, epithelial-to-mesenchymal transition, and DNA damage response as well as cell growth, invasion, and differentiation [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%